2022
DOI: 10.3389/fnut.2022.901006
|View full text |Cite
|
Sign up to set email alerts
|

Fat Oxidation of Fatty Fish vs. Meat Meal Diets Under in vitro Standardized Semi-Dynamic Gastric Digestion

Abstract: Meat and fish are introduced into the diet as a source of protein, but these muscle foods present different fatty acid (FA) compositions and different lipid stabilities. Fatty fish is expected to oxidize due to its higher content of polyunsaturated FA (PUFA), whereas the higher heme-Fe content of red meat will also affect lipid stability. Combining other food ingredients within a meal also influences lipid oxidation, which will not stop after meals intake. This is due to the acidic environment of the stomach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The bile emulsification will possibly increase the lipid droplets' surface area, which is susceptible to lipid peroxidation, increasing the generation of more aldehydes 53 . Several studies reported that the gastrointestinal digestion of foods with a moderate and high fat content led to the formation of toxic compounds, such as 4‐hydroxy‐trans‐2‐nonenal, 4‐hydroxy‐trans‐2‐hexenal, and malondialdehyde 56,57 . Martini et al 58 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bile emulsification will possibly increase the lipid droplets' surface area, which is susceptible to lipid peroxidation, increasing the generation of more aldehydes 53 . Several studies reported that the gastrointestinal digestion of foods with a moderate and high fat content led to the formation of toxic compounds, such as 4‐hydroxy‐trans‐2‐nonenal, 4‐hydroxy‐trans‐2‐hexenal, and malondialdehyde 56,57 . Martini et al 58 .…”
Section: Resultsmentioning
confidence: 99%
“…53 Several studies reported that the gastrointestinal digestion of foods with a moderate and high fat content led to the formation of toxic compounds, such as 4-hydroxy-trans-2-nonenal, 4-hydroxy-trans-2-hexenal, and malondialdehyde. 56,57 Martini et al 58 reported that, in grilled turkey meat with extra virgin olive oil (10%) added, the concentrations of TBARs and hydroperoxides increased during in vitro gastrointestinal digestion.…”
Section: Lipid Oxidation Of Beef Burgersmentioning
confidence: 99%
“…While this method represents a simplified digestive process, it has been employed in numerous studies [62,63]. Recent standardized in vitro digestion methods aim to simulate the physicochemical processes occurring in the human gastrointestinal tract (mouth, stomach, and small intestine) during food digestion [64][65][66][67]. Additionally, our study did not assess the expression of other metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Foods highly susceptible to lipid oxidation include oils and fats, fatty fish, nuts and seeds, dairy products, and meat [ 4 , 25 , 33 , 34 ]. Additionally, it would be useful to analyze the number of consumers that reject food products specifically due to rancidity and the reasons behind the rejection.…”
Section: Spoilage In Food: Oxidative Ranciditymentioning
confidence: 99%